THE INDISPENSABILITY OF THE EDUCATIONAL PLANNING PROCESS - Alves de Souza, Adriana; da Costa Alves, Ivanir; Martins da Silva Sousa, Leaci; Moreira da Silva, Jeromice (Revista Gênero e Interdisciplinaridade, 2024)
This article proposes an investigation into the relevance of the act of planning in the educational context, emphasizing its positive impact on the quality of teaching and the comprehensive development of students. Recognizing planning as a fundamental practice that permeates various dimensions of life, playing a decisive role in achieving goals and the effectiveness of actions, its expanded importance in the educational field is highlighted. In this context, planning directs strategies and guides actions that shape the teaching-learning process. The theoretical frameworks used include Vasconcellos (2019), Libâneo (2001; 2016), Veiga (1996), among others. The conduct of this study involved an exploratory, qualitative, and bibliographic research approach, seeking an in-depth understanding of the topic at hand. The research aimed to identify specific relevant points about the act of planning, with the intention of deepening the understanding of key related aspects. The literature analysis revealed that educational planning goes beyond the mere definition of activities to be carried out, standing out for its ability to promote efficient, meaningful education aligned with pedagogical objectives.